Isolation, Identification, and Antimicrobial Susceptibility of Uropathogenic Morganella Morganii - Auda, Jamela Gh.; Al-Grawi, Ibtesam Gh. (AL-Kindy College Medical Journal, 2009)
Background: Morganella morganii is one of the important nosocomial pathogens that may cause urinary tract infection and bacteremia.Methods: The above bacterium was identified from 250 bacterial strains which were isolated from 220 urine samples of patients with urinary tract infection. Antimicrobial susceptibility, by using disk diffusion method, of isolates was tested against some antibiotics.Results: Two M. moganii strains were isolated from female catheterized urinary tract patients, and identified by conventional biochemical tests and API20E system at the first time in Iraq. Both of them produced urease and hemolysin. Antimicrobial susceptibility test showed that these strains are resistant to, amoxicillin-clavulanate, cephalothin, gentamycin, tetracycline, trimethoprim-sulfamethaxzole, penicillin, and piperacillin, while they are sensitive to amikacin, ciprofloxacin, and norfloxacin.Conclusions: M. moganii one of opportunistic uropathogens, especially in catheterized patients. It has produced many virulence factors and exhibited multidrug resistance